Effect of Supplemental Antioxidant-Based Therapy on the Oxidative Stress Level in COVID-19 Patients - Zendelovska, Dragica; Atanasovska, Emilija; Spasovska, Katerina; Kirijas, Meri; Jakimovski, Dejan; Kapsarov, Kosta; Petrushevska, Marija (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2023)
Background: COVID-19 is a disease in several stages starting with virus replication to dysregulation in immune system response, organ failure and recovery/death. Our aim was to determine the effect of Ganoderma lucidum, lycopene, sulforaphane, royal jelly and resveratrol extract on markers of oxidative stress, inflammation, routine laboratory analyses and duration of symptoms in COVID-19 patients. Methods: The oxidative stress parameters and interleukines 6 and 8 (IL-6, IL-8), tumor necrosis factor alpha (TNF-α) were determined in order to estimate the antioxidant and the anti-inflammatory effect of the product using a spectrophotometric and a magnetic bead-based multiplex assay in serum of 30 patients with mild form of COVID-19. Results: Statistically significant differences were obtained for all investigated parameters between the treated patients and the control group. Moreover, significant differences were observed for leukocytes, neutrophil to leukocyte ratio and iron. The average duration of the symptoms was 9.4±0.487 days versus 13.1±0.483 days in the treatment and the control group, respectively (p=0.0003). Conclusion: Our results demonstrated the promising effect of Ge132+NaturalTM on reducing the oxidative stress and the IL-6, IL-8 and TNF-α levels, and symptoms duration in COVID-19 patients. The evidence presented herein suggest that the combination of Ganoderma lucidum extract, lycopene, sulforaphane, royal jelly and resveratrol could be used as a potent an adjuvant therapy in diseases accompanied by increased oxidative stress and inflammation.
Keywords: oxidative stress; anti-inflammatory; Ge132+ Natural™; Ganoderma lucidum; lycopene; sulforaphane; royal jelly; resveratrol; COVID-19